2009
DOI: 10.1525/mp.2009.26.5.475
|View full text |Cite
|
Sign up to set email alerts
|

Facial Expressions and Emotional Singing: A Study of Perception and Production with Motion Capture and Electromyography

Abstract: FACIAL EXPRESSIONS ARE USED IN MUSIC PERFORMANCE to communicate structural and emotional intentions. Exposure to emotional facial expressions also may lead to subtle facial movements that mirror those expressions. Seven participants were recorded with motion capture as they watched and imitated phrases of emotional singing. Four different participants were recorded using facial electromyography (EMG) while performing the same task. Participants saw and heard recordings of musical phrases sung with happy, sad, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 75 publications
(71 reference statements)
3
51
1
2
Order By: Relevance
“…' (p. 238) In the study presented here, it was hypothesized that if participants rated higher degrees of empathy, differences between recognition and felt ratings would decrease. Studies on emotional contagion sometimes access expressive facial muscle activation in listeners observing a performer (Livingstone, Thompson, & Russo, 2009). However, during music listening without visual display of performers' movements, measurement of internal mimicking of movements remains difficult.…”
Section: Empathy Emotional Contagion and Music Listeningmentioning
confidence: 99%
“…' (p. 238) In the study presented here, it was hypothesized that if participants rated higher degrees of empathy, differences between recognition and felt ratings would decrease. Studies on emotional contagion sometimes access expressive facial muscle activation in listeners observing a performer (Livingstone, Thompson, & Russo, 2009). However, during music listening without visual display of performers' movements, measurement of internal mimicking of movements remains difficult.…”
Section: Empathy Emotional Contagion and Music Listeningmentioning
confidence: 99%
“…Most recently, facial expressions in emotional singing may also use this code. Livingstone, Thompson, and Russo (2009) reported that singers' emotional intentions could be identified from specific facial features. Speech and music share many of the same features when expressing similar emotions (Juslin and Laukka 2003).…”
mentioning
confidence: 99%
“…Although musicians may be more focused on communicating the emotion in the production phase, production constraints associated with singing might limit the capacity of singers to express emotion through movements of the mouth. The findings of Livingstone et al (2009) suggest that the pre- and post-production epochs contain important movement information that singers use to communicate emotion through facial expressions made before and after singing. Perceivers appear to mimic the emotional expressions of singers (see also Chan et al, 2013) but it is unclear whether perceivers can use this information to accurately decode the intended emotion based solely on the motion information conveyed in point-light displays.…”
Section: Methodsmentioning
confidence: 99%